Nonlinear dynamics. Volume 1 : proceedings of the 35th IMAC, a Conference and Exposition on Structural Dynamics 2017 - Kerschen, G. (Springer, 2017)
Nonlinear Dynamics, Volume 1: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the first volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Nonlinear Dynamics, including papers on: Nonlinear System Identification Nonlinear Modeling & Simulation Nonlinear Reduced-order Modeling Nonlinearity in Practice Nonlinearity in Aerospace Systems Nonlinearity in Multi-Physics Systems Nonlinear Modes and Modal Interactions Experimental Nonlinear Dynamics.
Keywords: Nonlinear mechanics -- Congresses.; Structural dynamics -- Congresses.; elektronické knihy; electronic books